Appliance Therapy in Temporomandibular Disorders: A Review (Indian Journal of Forensic Medicine & Toxicology, 2020)
The prosthetic rehabilitation in temporomandibular disorders is a challenging task, This article reviews aboutthe present condition and provides the data regarding the treatment needs of the TMD patients and whatapproach should be followed the practitioner. There has been tremendous development in Evaluating throughMRI, it was inferred that the splint therapy through various means reduced the risk of the temporomandibulardisorders by eliminating the etiological factor. Furthermore it allowed the patient to cope with the diseasesuch as disk displacement with greater tolerance rate. Moreover, after treatment the patients are likely tocope with disc displacements with larger or smaller tolerance.